Penyuluhan pencegahan kebakaran hutan dan lahan pada kawasan gambut Kecamatan Dayun Kabupaten Siak Sri Indrapura - Ahmad Jamaan; Febri Yuliani; Adianto Adianto; Abdul Sadad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Forest and land fires in Indonesia have become a global problem due to their impact. In Riau alone, the area of burned land reached more than 42,000 hectares and had a negative impact on many fields such as transportation, education, health, trade, tourism, and even the running of government. Although many groups have been involved and various efforts have been made, until August 2019 fires were still frequent. This paper focuses on efforts to involve community groups, especially farmers in peatlands, actively participating in preventing fires. The community is given information and education to be able to cultivate the land without burning. In addition, the community is also trained so that the skills to strengthen their institutions through three aspects, namely technical, socio-cultural, and economic. This activity increases public awareness so that they are aware and aware of forest and land fires, the legal impact and losses that will be caused by land fires. The community is able to implement agricultural business through land clearing that is safe from fire and friendly to the environment and strengthening institutions. The community has also developed intercropping in the form of watermelons on their plantations.